Wastewater - Morgan, Sally (Norh Mankato, MN : Smart Apple Media, 2008)
Describes the different ways wastewater is created and explains how it is treated in sewage treatment plants and in less high-tech ways using reed beds and special ponds.
Using water -- Wastewater -- Treating sewage -- Sewage treatment plants -- Reed beds -- Desert sun and fishponds -- Industrial water -- Farm water -- Creating wildlife habitats -- Reusing and recycling water -- Way ahead -- Glossary -- Index.
Includes index.
9 - 12 years
Keywords: Water -- Purification -- Biological treatment; Sewage -- Purification -- Biological treatment